2017
DOI: 10.1111/jdi.12708
|View full text |Cite
|
Sign up to set email alerts
|

Clinical surrogate markers for predicting metabolic syndrome in middle‐aged and elderly Chinese

Abstract: Aims/IntroductionThe present study evaluated the ability of lipid accumulation product (LAP), visceral adiposity index (VAI), and the product of triglycerides and glucose (TyG), three novel markers, in identifying metabolic syndrome (MetS) with different criteria in middle‐aged and elderly Chinese.Materials and MethodsDuring June 2012 to January 2013, 992 consecutive patients (age ≥40 years) were enrolled at Daping Hospital. The criteria of MetS were based on the International Diabetes Federation and the modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
48
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 30 publications
(68 reference statements)
9
48
3
1
Order By: Relevance
“…compared the TyG index with the euglycemic‐hyperinsulinemic clamp test, and suggested that TyG could be useful for the identification of individuals with decreased insulin sensitivity in 2010 . A series of cohort and cross‐sectional studies confirmed a strong correlation between the TyG index and IR, type 2 diabetes mellitus, MetS, hypertension, cardiovascular events and fatty liver both in China and elsewhere. Published studies have shown that the TyG index is helpful for the prediction and early identification of individuals at high risk of cardiometabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…compared the TyG index with the euglycemic‐hyperinsulinemic clamp test, and suggested that TyG could be useful for the identification of individuals with decreased insulin sensitivity in 2010 . A series of cohort and cross‐sectional studies confirmed a strong correlation between the TyG index and IR, type 2 diabetes mellitus, MetS, hypertension, cardiovascular events and fatty liver both in China and elsewhere. Published studies have shown that the TyG index is helpful for the prediction and early identification of individuals at high risk of cardiometabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that the TyG index is tied to metabolic diseases and CVD [10,11]. The TyG index has been considered a reliable biomarker for predicting type 2 diabetes mellitus (T2DM) and metabolic syndrome (MS) [12,13]. Several studies have even reported that the TyG index is a better predictor for coronary artery atherosclerosis and arterial stiffness when compared with HOMA-IR [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Serum gamma-glutamyl transferase was positively associated with MetS and its components in Korean children and adolescents, and could be a useful measure for identifying young people with MetS 3 . Another study found that lipid accumulation product, visceral adiposity index, and the products of triglycerides and glucose were reliable novel surrogate markers for identifying MetS in middle-aged and elderly Chinese individuals 4 . Elevated circulating member B levels of the family with sequence similarity 3 might be a predictor of MetS onset and progression 5 .…”
Section: Predictors and Markers Of Obesity And Mets In Asiamentioning
confidence: 99%